Simple and Efficient Synthesis of Anithiactins A‐C, Thiasporine A and Their Potent Antitumor 2, 4‐Linked Oligothiazole Derivatives. Issue 2 (15th January 2019) - Liu, Yi; Ma, Zhanwei; Zhao, Xiangyun; Shan, Qiuli; He, Peng; Du, Yuguo; Wang, Yibin
Abstract: Directly 2, 4‐linked oligothiazoles are not only broadly applied in drug discovery but also are the core structural motif of many biological natural products. With this background, we reported a simple and efficient route for the synthesis of four 2‐phenylthiazole natural products anithiactins A−C, thiasporine A, and series of their novel 2, 4‐linked oligothiazole derivatives relies on the one‐pot cascade reaction of β ‐azido disulfides and commercially carboxyl acids. This approach also represented a remarkably direct and simple route for 2, 4‐linked oligothiazoles synthesis. By doing so, ten bisthiazoles and terthiazoles were effectively obtained in only 3∼6 linear steps with good to moderate yields. The bioassay results demonstrated that all the phenyl‐based oligothiazoles show potent antitumor activities. Among them, terthiazole 28 was the most potent compound with IC50 values of 4.4 μM, 4.8 μM against HCT116 and A549 cell lines, respectively. Abstract : A simple and efficient route for the synthesis of four 2‐phenylthiazole natural products anithiactins A−C, thiasporine A, and series of their novel 2, 4‐linked oligothiazole derivatives was developed. Ten bisthiazoles and terthiazoles were effectively obtained in only 3∼6 linear steps with good to moderate yields. The bioassay results demonstrated that all phenyl‐based oligothiazoles exhibited potent antitumor activities. Among of them, terthiazole 28 was the most potent compound with IC50 values of 4.4 μM, 4.8 μM against HCT116 and A549 cell lines, respectively.